STRATEGI PEMASARAN KREDIT USAHA RAKYAT (KUR) PT. PEGADAIAN UNIT PEMBANTU CABANG (UPC) RANCABALI - Rahmalia, Mutia; Maryati; Ma’mun, Saepul (Jurnal Pelita Nusa, 2025)
This study aims to analyze the marketing strategy of Sharia People’s Business Credit (KUR Syariah) at PT. Pegadaian, Rancabali Auxiliary Branch Unit (UPC), and its impact on increasing customer income. KUR Syariah is a sharia-based financing facility provided to productive business actors to support business development. This research employed a descriptive qualitative method, with data collected through interviews, observations, and documentation. The findings indicate that the marketing strategies implemented include brochure distribution, direct selling or call calling, market outreach activities, direct visits to residents’ homes and MSMEs, and socialization of KUR Syariah products. The implementation of KUR Syariah has positively contributed to increasing customer income through easier access to financing, improved productivity and business expansion, strengthening the local economy, and enhancing sharia financial literacy. These positive impacts are reflected in changes in customers’ attitudes toward managing their businesses more diligently, responsibly, and sustainably. However, several obstacles were identified, including low public interest, perceptions of relatively strict requirements, comparisons with other financial institutions, limited immediate capital needs, and incomplete customer documentation.